Grammarly AI as a Smart Feedback System: Students’ Perspectives on Writing Improvement and Plagiarism Avoidance in Digital Learning (International Forum of Researchers and Lecturers, 2026)
This study examines how Grammarly AI helps students improve their writing and avoid plagiarism in digital learning. As more academic work is done online, students need quick and clear feedback to guide their revisions. This research focuses on students’ perceptions of Grammarly and how they respond to its feedback. A survey was conducted with 30 university students using Likert scale and open-ended questions. The results show that most students find Grammarly helpful for correcting grammar, improving clarity, and motivating them to revise their writing. Students also reported that the paraphrasing and similarity checking features help them maintain originality and understand academic integrity better. These findings are supported by the Technology Acceptance Model (TAM), which explains that students respond positively when a tool is useful and easy to use, and by feedback theory, which highlights how learners process corrective input. Overall, this study concludes that Grammarly functions not only as an error-correction tool but also as a learning support system that strengthens writing skills and promotes responsible writing practices in digital environments.